Nutrient Requirement of Egg and Meat Type Duck - Pius P Ketaren (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
Ducks in Indonesia play roles in producing egg and meat. More than 19% of egg consumption were produced by ducks, however as meat source they only contributed 0.94% of total meat supply in Indonesia. Feed and feeding management are very important in duck farming as 70% of total production cost of egg and meat-type ducks accounted for  feed cost. Unfortunately, nutrient requirements for the Indonesian ducks were limited. Therefore, overseas nutrient recommendation may be used. Water is the most important nutrient for poultry including duck, therefore quantity and quality of water are very important to be considered in feeding ducks. There are various local feeds available in Indonesia to be used as duck diets. Quality of feed is very important in duck farm as the ducks is very sensitive to aflatoxin poison. The maximum safe level of aflatoxin in the diet was to be less than 40 µg/kg.   Key words. Duck, egg, meat, feed and nutrient